Cloaca in Discordant Monoamniotic Twins: Prenatal Diagnosis and Consequence for Fetal Lung Development - Chitrit, Yvon; Vuillard, Edith; Khung, Sunavy; Belarbi, Nadia; Guimiot, Fabien; Muller, Francoise; Ghoneimi, Alaa El; Oury, Jean Francois (American Journal of Perinatology Reports, 2014)
Objective Describe a case of cloaca prenatally diagnosed in one of a set of monoamniotic twins.Study Design Retrospective review of a case.Results Cloaca is one of the most complex and severe degrees of anorectal malformations in girls. We present a discordant cloaca in monoamniotic twins. Fetal ultrasound showed a female fetus with a pelvic midline cystic mass, a phallus-like structure, a probable anorectal atresia with absence of anal dimple and a flat perineum, and renal anomalies. The diagnosis was confirmed by fetal magnetic resonance imaging postnatally.Conclusions The rarity of the malformation in a monoamniotic pregnancy, the difficulties of prenatal diagnosis, the pathogenic assumptions, and the consequences of adequate amniotic fluid for fetal lung development are discussed.
Keywords: prenatal diagnosis; persistent cloaca; monoamniotic twins; fetal lung development; discordant